Secure Pesticide Storage: Essential Structural Features of a Storage Building - Thomas W. Dean (EDIS)
This document identifies and describes five structural features that should be present in any building constructed for pesticide storage. This document is Fact Sheet PI-30, part of a series from the Pesticide Information Office, Food Science and Human Nutrition Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: April 2004. Revised: November 2004.